Evaluation of the Effect of Health Sector Evolution Plan on the Rate of Cesarean Sections in Hospitals Affiliated to Abadan School of Medical Sciences - Jamshid Bahmaei; Anahita Maleki (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: One of the health sector evolution plan's goals is to reduce the rate of cesarean section (C-section) and increase the natural childbirth rate. Therefore, this study aimed to evaluate the rate of C-sections before and after the implementation of the health sector evolution plan in the hospitals affiliated to Abadan School of Medical Sciences, Abadan, Iran. Methods: The study population of this descriptive-analytical study included all hospitals with a maternity ward affiliated to Abadan School of Medical Sciences. The samples were selected using a census method. The C-section rates were evaluated in 2013 and 2018 to calculate the baseline C-section rate at the beginning and five-year after the implementation of the plan, respectively. In order to investigate the effect of the health sector evolution plan on the mean cost spent by mothers, it was studied in one hospital. The data were analyzed in SPSS  software (version 18) using the Chi-square test, and Paired t-test. Results: The total C-section rate was 45% as the baseline cesarean rate in 2013, which decreased by 24.44% to 34% during the 5 years after the plan. The mean cost spent by each hospitalized mother was 103342.175 Rials prior to the implementation of the health sector evolution plan which was reduced to 96689.4347 Rials after the implementation of the plan. Conclusion: According to the results, there was a reduction in the rate of C-sections after the implementation of the health sector evolution plan in hospitals under study. However, regarding the global rate of C-sections, the mean C-section rate is still high in these hospitals.